PENGEMBANGAN APLIKASI INSTRUMEN GAMELAN GONG KEBYAR BERBASIS ANDROID - I Putu Surya Pratama Wardhana; I Gede Mahendra Darmawiguna; I Made Gede Sunarya (KARMAPATI (Kumpulan Artikel Mahasiswa Pendidikan Teknik Informatika), 2014)
Gong Kebyar is one of barunganBali’s "pelog lima nada"-harmonized gamelangroups which the playing technique uses kebyarsystem. The gamelan Gong Kebyar instrumentsof application is software that simulates theGong Kebyar instruments so that it can beoperated on the Android operating system. Thisresearch aims to design and implement a draftapplication of gamelan Gong instrumentsAndroid-based.The gamelan Gong Kebyar instruments ofapplications Android-based is developed by usingthe software development life cycle in the form ofa linear or sequential waterfall model. The mainfeatures of this application are to play thegamelan Gong Kebyar instruments, additionallythere are video features so that users know howto play the actual/real instruments. Theapplication is design by using a functional modelof a UML (Unified Modeling Languange) andimplemented by the Java programming languageusing Eclipse as editor, plug-ins ADT (AndroidDevelopment Tools) and AndEngine asadditional libraries.The results of this research, is gamelanGong Kebyar instruments of applications basedon Android that has been successfully developed.The entire functional requirements have beensuccessfully implemented in accordance with thedraft.